Local Knowledge/Lacking Knowledge: Contradictions in Participatory Agroecology Development in Bolivia - Cockburn, Jenny (Anthropologica, 2015)
Questions of who is understood to have agricultural knowledge, and how this perception influences knowledge exchange, uncover power imbalances in local, national and international relations. Analysis of fieldwork in Norte de Potosi, Bolivia, finds that NGO and state agronomists position themselves as teachers to farmer-students, masked by participatory language. Barriers to knowledge exchange and collaboration remain stubbornly entrenched even in efforts to transcend power relations and improve participatory approaches. Ironically, agronomists are positioned to hold both "expert" and "local" knowledge, which is then repackaged within agroecology. Meanwhile, farmers using compliant discourse (some times strategically) continue to be positioned as lacking.